Investigations on bubbly two-phase flow in a constricted vertical pipe. (September 2020) - Neumann-Kipping, Martin; Bieberle, André; Hampel, Uwe
Highlights: Experimental benchmark data of 3D gas-liquid two-phase flow fields in a pipe Flow field analyses of two flow constrictions halving the pipes cross-section Ultrafast X-ray imaging for investigations on phase distributions and bubble sizes Enhanced CT data processing suppresses image artifacts effectively Flow field analysis for constant gas and various liquid superficial velocities Abstract: We report on an experimental investigation of adiabatic bubbly two-phase flow development in a DN50 pipe with a ring-shaped and a baffle-shaped constriction at different superficial velocities of gas (up to j g = 0.1400 m·s −1 ) and liquid (up to j l = 1.6110 m·s -1 ) using ultrafast electron beam X-ray computed tomography (UFXCT). From UFXCT images, cross-sectional gas holdup distributions were obtained with a temporal resolution of up to 2, 500 frames per second in 18 scanning planes along the pipe. A sophisticated data processing approach was applied to extract gas holdup data immediately from the two-phase flow image stack. Based on that, time-averaged gas holdup of the cross-section and the axial center of the pipe were calculated. In addition, bubble sizes and velocities were determined.